Bile acid accumulation induced by miR-122 deficiency in liver parenchyma promotes cancer cell growth in hepatocellular carcinoma - Jia-Hui Huang; Yi-Hang Li; Juan-Zhen Hong; Ruo-Nan Li; Ruizhi Wang; Zi-Qi Chen; Song-Yang Li; Ying-Lei Chi; Jin-Yu Huang; Ying Zhu (Molecular Therapy: Nucleic Acids)
Liver is the central player in maintaining metabolic homeostasis of bile acids (BAs), but how BA is tightly controlled is still largely unknown, and the role of BAs in the development of hepatocellular carcinoma (HCC) remains controversial. Here, we discovered that elevated hepatic BAs were associated with miR-122 downregulation during liver regeneration, steatosis, and fibrosis. In vivo mouse models showed that miR-122 deficiency of liver parenchymal cells (hepatocytes) in paracancerous tissues resulted in significantly increased BA levels and altered hepatic BA spectrum, thus promoting liver tumor burden, which could be abated by administration of BA sequestrant. Mechanistically, miR-122 attenuated BA production by directly targeting BA synthesis gene HSD3B7, thereby inhibiting cancer cell proliferation and HCC growth. Overexpression of HSD3B7 in hepatocytes abolished the inhibitory effect of intrahepatic delivery of miR-122 on cancer cell proliferation in c-Myc/sgTP53-induced HCC model. Consistently, lower miR-122 was associated with elevated levels of BA and HSD3B7 protein in paracancerous tissues from HCC patients and also associated with worse overall survival of HCC patients. These findings provide novel insights into the roles of miR-122-mediated BA regulatory network of liver parenchymal cells of tumor microenvironment during HCC progression, which may provide attractive therapeutic targets for HCC.